Betanodavirus Infection in Barramundi in Riau Islands - Rifai, Achmad Bahtiar; Wulandari, Titis; Surastini, Desi; Irawanto, Pramudya Dwi Wahyu (Universitas Airlangga, 2022)
Diseases that can cause very high economic losses are viruses and one of them is Betanodavirus or commonly called Viral Nervous Necrosis (VNN). VNN is a disease registered by The Office International des Epizooties (OIE) and is a major problem in marine fishery production in the world. This virus is able to infect fish from larva size to consumption size in a short period of time to reach death with a frequency of 80% to 100%. The disease can infect barramundi and is spread throughout the Riau Islands. This study used a live fish sampling method showing VNN signs and freshly dead fish. The research samples were obtained from several cities and districts in the Riau Islands Province, including Batam City, Bintan Regency, and Tanjung Balai Karimun Regency, the sample selection was based on clinical symptoms and fish mortality. Then the samples were necropsied for eye and brain organs, then amplified using primers targeting the RNA 2 gene. The results showed that VNN had been detected in the Riau Islands Province, i.e. Batam City, Bintan Regency, and Tanjung Balai Karimun Regency.